âˆ’174 G/C polymorphism of interleukin 6 gene is not significantly different in Turkish professional short and long distance runners - Arica, Secil; Solgun, Huseyin Avni; Demirel Dengi, Ayse Seda; Bakmaz, Enver; Akçay, Teoman; Kapici, Sezgin; Sercan, Canan; Ulucan, Korkut (Cellular and Molecular Biology, 2018)
Interleukin-6 (IL-6) is a kind of multifunctional cytokine and involved in mediating muscle repair metabolism, and therefore athletic capacity. Muscular and circulating IL-6 levels increase in response to physical exercise. Responsible gene coding for IL-6 has a functional polymorphism in its promoter region, -174 G/C (rs1800795). We aimed to analyze the association of G allele and GG genotype in Turkish professional athletes and compare the allelic and genotypic difference between short distance and long distance runners. For this purpose, we enrolled 40 (24 short distance runners and 16 long distance runners) Turkish professional athletes to the study. Real time genotyping procedure was carried out to determine the -174 G/C polymorphism. G allele and GG genotype was more prevalent than the others in our cohort. We found no statistically significant difference between short and long distance runners in the terms of genotype (p=0.07). Our study suggests that-174 G/C polymorphism of IL-6 gene differs in athletes, G allele and GG genotype is higher than the other ones, at least in Turkish athletes, and therefore should be taken into consideration when determining genetic aspects of athletes. Further studies are necessary to confirm our results and show the effect of the given polymorphism in sports science.